The Influence of Earnings Per Share and Price to Book Value On Stock Prices for The 2019-2021 (Case Study of an Automotive Sub-Sector Company on IDX) - Utomo, Agus Setyo; Partini, Sri (Nur Science Institute, 2024)
The phenomenon that occurred during the Covid 19 pandemic which broke out in Indonesia at the beginning of 2020 had an impact on all aspects of life, including the capital market. The spread of Covid-19 in Indonesia has caused fear among investors, so many of them have chosen to abandon risky assets. This affects the movement of the Composite Stock Price Index (IHSG). The problem in this research aims to determine the influence of EPS (Earning Per Share) and PBV (Price To Book Value) on share prices in automotive companies listed on the IDX for the 2019 - 2021 period. The type of research used is quantitative research with secondary data sources. The population in this research is 15 automotive companies listed on the Indonesia Stock Exchange for the 2019 - 2021 period. Sampling used a purposive sampling technique of 10 companies that met the criteria. The data analysis technique uses multiple linear regression analysis techniques. The results of the research show that EPS is able to influence share prices, and also influences share prices, and PBV influences company share prices . Simultaneously, the EPS (Earning Per Share) and PBV (Price To Book Value) variables influence stock prices.